Prevalence and frequency of menstrual cycle symptoms are associated with availability to train and compete: a study of 6812 exercising women recruited using the Strava exercise app. Issue 8 (16th November 2020) - Bruinvels, Georgie; Goldsmith, Esther; Blagrove, Richard; Simpkin, Andrew; Lewis, Nathan; Morton, Katie; Suppiah, Ara; Rogers, John P; Ackerman, Kathryn E; Newell, John; Pedlar, Charles
Abstract : Objectives: The menstrual cycle can affect sports participation and exercise performance. There are very few data on specific menstrual cycle symptoms (symptoms during various phases of the cycle, not only during menstruation) experienced by exercising women. We aimed to characterise the most common symptoms, as well as the number and frequency of symptoms, and evaluate whether menstrual cycle symptoms are associated with sporting outcomes. Methods: 6812 adult women of reproductive age (mean age: 38.3 (8.7) years) who were not using combined hormonal contraception were recruited via the Strava exercise app user database and completed a 39-part survey. Respondents were from seven geographical areas, and the questions were translated and localised to each region (Brazil, n=892; France, n=1355; Germany, n=839; Spain, n=834; UK and Ireland, n=1350; and USA, n=1542). The survey captured exercise behaviours, current menstrual status, presence and frequency of menstrual cycle symptoms, medication use for symptoms, perceived effects of the menstrual cycle on exercise and work behaviours, and history of hormonal contraception use. We propose a novel Menstrual Symptom index (MSi) based on the presence and frequency of 18 commonly reported symptoms (range 0–54, where 54 would correspond to all 18 symptoms each occurring very frequently). Results: The most prevalent menstrual cycle symptoms were mood changes/anxiety (90.6%), tiredness/fatigue (86.2%), stomach cramps (84.2%) and breast pain/tenderness (83.1%). After controlling for body mass index, training volume and age, the MSi was associated with a greater likelihood of missing or changing training (OR=1.09 (CI 1.08 to 1.10); p≤0.05), missing a sporting event/competition (OR=1.07 (CI 1.06 to 1.08); p≤0.05), absenteeism from work/academia (OR=1.08 (CI 1.07 to 1.09); p≤0.05) and use of pain medication (OR=1.09 (CI 1.08 to 1.09); p≤0.05). Conclusion: Menstrual cycle symptoms are very common in exercising women, and women report that these symptoms compromise their exercise participation and work capacity. The MSi needs to be formally validated (psychometrics); at present, it provides an easy way to quantify the frequency of menstrual cycle symptoms.